Pectinase production by a Brazilian thermophilic fungus Thermomucor indicae-seudaticae N31 in solid-state and submerged fermentation - Martin, N. [UNESP]; Guez, M. A. U. [UNESP]; Sette, L. D.; Da Silva, R. [UNESP]; Gomes, E. [UNESP] (Maik Nauka/interperiodica/springer, 2010)
Thermophilic organisms produce thermostable enzymes, which have a number of applications, justifying the interest in the isolation of new thermophilic strains and study of their enzymes. Thirty-four thermophilic and thermotolerant fungal strains were isolated from soil, organic compost, and an industrial waste pile based on their ability to grow at 45A degrees C and in a liquid medium containing pectin as the only carbon source. Among these fungi, 50% were identified at the genus level as Thermomyces, Aspergillus, Monascus, Chaetomium, Neosartoria, Scopulariopsis, and Thermomucor. All isolated strains produced pectinase during solid-state fermentation (SSF). The highest polygalacturonase (PG) activity was obtained in the culture medium of thermophilic strain N31 identified as Thermomucor indicae-seudaticae. Under SSF conditions on media containing a mixture of wheat bran and orange bagasse (1 : 1) at 70% of initial moisture, this fungus produced the maximum of 120 U/ml of exo-PG, while in submerged fermentation (SmF) it produced 13.6 U/ml. The crude PG from SmF was more thermostable than that from SSF and exhibited higher stability in acidic pH.
Keywords: pectinase; Thermophilic fungi; Thermomucor; Fermentation; Thermostable enzyme; Polygalacturonase